A narrativa entre aspas de Bernardo Carvalho: legitimação e paratopia em um estudo de Onze: uma história - Paulo César Silva de Oliveira (Universidade de Brasília, 2011)
The paratopic situation of the Latin American writer and the legitimating process are the starting point of this article, concentrated on the analysis of the novel Onze: uma história , by Bernardo Carvalho. The connections between local and global; author policies and text policies; as well as the place held by the Brazilian fiction in the contemporary scenario will be investigated inside Bernardo Carvalho’s textual machine, aiming at establishing limits and reaches of his writings regarding a modernity constituted by displacements, border crossings, and the dilution of political, geographical and fictional frontiers.